Significantly improved de/rehydrogenation properties of lithium borohydride modified with hexagonal boron nitride1. Issue 63 (10th July 2015) - Tu, Guoping; Xiao, Xuezhang; Qin, Teng; Jiang, Yiqun; Li, Shouquan; Ge, Hongwei; Chen, Lixin
<x xml:space="preserve">Abstract</x> The dehydrogenation kinetics of LiBH4 could be significantly improved by doped with h-BN. For the 30 mol% h-BN doped LiBH4, 12.6 wt% hydrogen could be released with in 2 h.